2011
DOI: 10.1097/hjh.0b013e328344da5e
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in artery wall biomechanical properties throughout life

Abstract: Elevated large artery stiffness and pulse pressure have emerged as important risk factors for cardiovascular disease. The genders differ in large artery biomechanical properties throughout the lifespan with females displaying higher stiffness than males during the prepubertal years and a dramatic increase after menopause. Males on the other hand experience an increase in arterial stiffness postpuberty and a linear increase thereafter, suggesting that females have intrinsically stiffer large arteries than males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
91
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(96 citation statements)
references
References 135 publications
(140 reference statements)
4
91
0
1
Order By: Relevance
“…One study in a healthy population of children between the ages of 3 to 18 years, reported that PWV remained unchanged during childhood but started to increase in girls at 10.4 years and in boys at 12.1 year, 42 suggesting an influence of pubertal status rather than age. 45 Sex and pubertal status, through changes in vasoactive hormone concentrations, are critical factors known to influence arterial wall properties and function. 45,46 Although age and sex was often matched or controlled for in the 15 studies analyzed in this review, pubertal status was not, except for one study that assessed children at a Tanner stage ≥II.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study in a healthy population of children between the ages of 3 to 18 years, reported that PWV remained unchanged during childhood but started to increase in girls at 10.4 years and in boys at 12.1 year, 42 suggesting an influence of pubertal status rather than age. 45 Sex and pubertal status, through changes in vasoactive hormone concentrations, are critical factors known to influence arterial wall properties and function. 45,46 Although age and sex was often matched or controlled for in the 15 studies analyzed in this review, pubertal status was not, except for one study that assessed children at a Tanner stage ≥II.…”
Section: Discussionmentioning
confidence: 99%
“…45 Sex and pubertal status, through changes in vasoactive hormone concentrations, are critical factors known to influence arterial wall properties and function. 45,46 Although age and sex was often matched or controlled for in the 15 studies analyzed in this review, pubertal status was not, except for one study that assessed children at a Tanner stage ≥II. 24 Furthermore, the time course of pathological adaptation (increased arterial stiffness) to obesity is not known, and it is unclear how age, sex, or pubertal status may interact with obesity and affect arterial stiffness in children.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have not found any difference in age-related aortic stiffening between men and women (Heijden-Spek et al 2000; Smulyan et al 2001); however, other studies have suggested a pronounced age-related increase in aortic stiffness in women more than men, mainly during menopause (Waddell et al 2001;Vermeersch et al 2008). These discordant findings have been ascribed to an intrinsic difference in arterial properties between men and women, possibly influenced by sex steroids (Waddell et al 2001;Rossi et al 2011), which may be emphasized in the presence of high BP (Boutouyrie and Vermeersch 2010) or other CV risks such as obesity and diabetes (Rossi et al 2011). Our results were adjusted for the classic CV risk factors by a forward stepwise multiple regression analysis; however, gender remained correlated with PWV only in normotensive subjects with other risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…This finding might be due the taller subjects in CON, since AIx, but not aPWV decreases with increasing height [35]. Another explanation might be the higher percentage of females in the INT-group, since females display higher stiffness than males during the pre-pubertal years [36]. Similarly, a study by Lurbe et al [37] including children from 7 to 18 years reported a higher augmentation index in females compared to males.…”
Section: Discussionmentioning
confidence: 90%